Reversible C−H activation, facile C−B/B−H metathesis and apparent hydroboration catalysis by a dimethylxanthene‐based frustrated Lewis pair - Vasko, P; Zulkifly, I; Fuentes, M; Mo, Z; Hicks, J; Kamer, P; Aldridge, S (Wiley, 2018)
A dimethylxanthene‐based phosphine/borane frustrated Lewis pair (FLP) is shown to effect reversible C−H activation, cleaving phenylacetylene, PhCCH, to give an equilibrium mixture of the free FLP and phosphonium acetylide in CD2Cl2 solution at room temperature. This system also reacts with B−H bonds although in a different fashion: reactions with HBpin and HBcat proceed via C−B/B−H metathesis, leading to replacement of the ‐B(C6F5)2 Lewis acid component by ‐Bpin/‐Bcat, and transfer of HB(C6F5)2 to the phosphine Lewis base. This transformation underpins the ability of the FLP to catalyze the hydroboration of alkynes by HBpin: the active species is derived from the HB(C6F5)2fragment generated in this exchange process.